Spatial mapping of flow-induced molecular alignment in a noncrystalline biopolymer fluid using double quantum filtered (DQF) 23Na MRI - Pavlovskaya, Galina E.; Meersmann, Thomas (American Chemical Society, 2014)
Flow-induced molecular alignment was observed experimentally in a non-liquid- crystalline bioplymeric fluid during developed tubular flow. The fluid was comprised of rigid rods of the polysaccharide xanthan and exhibited shear-thinning behavior. Without a requirement for optical transparency or the need for an added tracer, 23Na magic angle (MA) double quantum filtered (DQF) magnetic resonance imaging (MRI) enabled the mapping of the anisotropic molecular arrangement under flow conditions. A regional net molecular alignment was found in areas of high shear values in the vicinity of the tube wall. Furthermore, the xanthan molecules resumed random orientations after the cessation of flow. The observed flow-induced molecular alignment was correlated with the rheological properties of the fluid. The work demonstrates the ability of 23Na MA DQF magnetic resonance to provide a valuable molecular-mechanical link.